Efforts to Increase Knowledge of Pregnant Women Through Education about HIV/AIDS Disease - Anggrawati Wulandari; Retno Palupi Yonni Siwi; Erma Retnaningtyas; Sri Yeni; Titin Wahyuni Batamba; Irawati (Journal of Community Engagement in Health, 2024)
The number of female HIV/AIDS sufferers is increasing along with the increase in transmission of unsafe sexual behavior in men who then transmit HIV to their sexual partners. In addition, HIV transmission from HIV-infected mothers to their babies tends to increase along with the increase in the number of HIV-infected women, which is why HIV/AIDS requires serious attention from parties involved in front-line health services. This community service is to increase pregnant women's knowledge about HIV/AIDS. This activity was carried out by providing counseling with leaflets to pregnant women about HIV/AIDS by giving a pre-test before counseling and a post-test after counseling. The technique is accidental sampling. The results of the counseling were obtained before the counseling was given as many as 2 participants (25%) with sufficient knowledge and after the activity there was an increase to 6 participants (75%) with Good knowledge.It is hoped that further education will focus on preventing HIV/AIDS in pregnant women.